An Overview of Hydrometeorological Disaster Preparedness in the Community of Bengawan Jero Area, Lamongan Regency : Original Article - Hidayati, Nur; Auliah, Fadilah; Kusbiantoro, Dadang; Jorkasi, Zuraida binti (Babali Publisher, 2024)
Introduction: Bengawan Jero is an area encompassing six districts: Turi, Karanggeneng, Kalitengah, Karangbinangun, Glagah, and Deket, which are highly susceptible to flood disasters. Disaster preparedness is crucial for ensuring community safety in facing such events. The aim of this study is to assess the preparedness of the community in the Bengawan Jero area in dealing with flood and tornado disasters. Method: This research employed a quantitative descriptive design and conducted with 333 participants selected using cluster random sampling. This study was conducted in the Bengawan Jero area, specifically in the Turi and Kalitengah districts of Lamongan Regency, in February 2024. A questionnaire on flood and tornado disaster preparedness was utilized to obtained the data, which previously validated with Cronbach’s alpha values of 0.932 and 0.954 respectively, and reliability coefficients of r = 0.444. Data analysis was performed descriptively. Result: The research findings indicate that 84% of the community demonstrated a readiness level categorized as “very prepared” in facing flood disasters, while 61% showed a readiness level categorized as “prepared” in dealing with tornado disasters. Conclusion: The level of community preparedness in facing hydrometeorological disasters is higher in the Kalitengah district compared to the Turi district. It is necessary to identify the factors contributing to the lower level of preparedness among the community in the Turi district.